Bioakumulasi Logam Berat (Pb) pada Vegetasi Mangrove Famili Rhizophoraceae di Teluk Lembar Kabupaten Lombok Barat - Rahman, Firman Ali; Listari, Nening; Jannah, Siti Wardatul (Bioscientist : Jurnal Ilmiah Biologi, 2022)
Mangroves are one of the coastal vegetations that have ecological roles and benefits as disaster mitigation, one of which is the bioaccumulation of lead (Pb) heavy metal contamination. The purpose of this study was to determine the uptake ability of the heavy metal lead (Pb) by mangrove leaf and root tissues, and the potential storage capacity of the heavy metal lead (Pb) in the substrate of the mangrove ecosystem found under stands of each type of mangrove in the Rhizophoraceae family. The research was conducted on the mangrove ecosystem of the Lembar Bay of West Lombok Regency. This research is a quantitative descriptive research using purposive random sampling method, which starts with taking samples of leaves and roots of each different species and taking samples of the substrate found under stands of mangrove species in the Rhizophoraceae family. Sample testing was carried out using the Atomic Absorption Spectrophotometer (AAS) method. The results showed that the heavy metal (Pb) content in the root tissue was greater than the test results on the leaf samples, namely the roots of Bruguiera gymnorrhiza of 7.23 ppm, the roots of Rhizophora stylosa of 2.84 ppm, and the roots of Ceriops decandra. of 2.84 ppm, while for Rhizophora stylosa leaves it was 4.23 ppm, for Bruguiera gymnorrhiza leaves it was 2.92 ppm, and for Ceriops decandra leaves it was 2.91 ppm. In addition, the content of heavy metal deposits found under the Bruguiera gymnorrhiza mangrove stands was 19.64 ppm, rhizophora stylosa substrate was 16.94 ppm, and 12.94 ppm ceriops decandra substrate. Meanwhile, based on the phytoremediation ability of mangrove species in the Rhizophoraceae family of the Sheet Bay mangrove ecosystem, it was found that the leaves of the type Rhizophora stylosa (- 1.24), were higher than those of Bruguiera gymnorrhiza (- 0.26), and Ceriops decandra (0.20). Similarly, the ability of root tissue as a phytoremediation agent was found to be greatest in Rhizophora stylosa (- 1.32).